Pengaruh Live Streaming TikTok Terhadap Keputusan Pembelian Produk Skintific Pada Generasi Z Pengikut Akun @skintific_id - Anindasari, Adeliya Putri; Tranggono, Didiek (Jurnal Ilmiah Wahana Pendidikan, 2023)
One of the popular and rapidly growing social media platforms is TikTok. The platform offers live streaming features that allow sellers to interact directly with potential buyers in promoting their products. This study aims to examine the influence of TikTok live streaming (including streamer credibility, media richness, and interactivity) on the purchasing decisions of Skintific products among Generation Z followers of the official TikTok account @skintific_id. The survey method was employed, distributing questionnaires to the followers of the account who belong to Generation Z. The findings indicate that TikTok live streaming has a significant and positive influence on the purchasing decisions of Skintific products. The variables of streamer credibility and media richness have a strong and positive influence on purchasing decisions, while the interactivity variable has a moderate and positive influence. Overall, the live streaming variables collectively have a significant influence on purchasing decisions. The conclusion of this study states that TikTok live streaming can be an effective strategy in influencing purchasing decisions for products, especially among Generation Z, who are active TikTok users. This research provides a deeper understanding of the importance of TikTok live streaming in product marketing, particularly in the beauty industry.